2005
DOI: 10.1016/j.immuni.2005.03.014
|View full text |Cite
|
Sign up to set email alerts
|

TCR Signal Strength Influences αβ/γδ Lineage Fate

Abstract: Signals transduced by T cell antigen receptors (TCRs) have been shown to be critical for alphabeta and gammadelta T cell development, but their role in lineage determination remains poorly defined. Two models have been forwarded for alphabeta/gammadelta lineage choice: the instructive model and the stochastic model. Recent data, however, are inconsistent with either model. In this study, we devised an experimental system in which lineage fate was controlled exclusively by the gammadeltaTCR. We then analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
270
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(289 citation statements)
references
References 46 publications
14
270
5
Order By: Relevance
“…Thus, signal strength does not only determine the outcome of positive and negative selection of DP cells; it appears also to be an important feature of b-selection. It has been suggested that strong and weak signals at the b-selection checkpoint favor development towards the cd and ab T cell lineages, respectively [25,26]. Our data is in agreement with this conclusion in that a certain minimal signal strength is required for facilitating b-selection through the ab (HY-) TCR.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, signal strength does not only determine the outcome of positive and negative selection of DP cells; it appears also to be an important feature of b-selection. It has been suggested that strong and weak signals at the b-selection checkpoint favor development towards the cd and ab T cell lineages, respectively [25,26]. Our data is in agreement with this conclusion in that a certain minimal signal strength is required for facilitating b-selection through the ab (HY-) TCR.…”
Section: Discussionsupporting
confidence: 91%
“…It was also observed that IL-17-producing ␥/␦ T cells are hardly induced in immunized joints, their DLNs, non-DLNs, and spleens of SKG mice (data not shown) 10 days after immunization with CFA plus type II collagen. Given that TCR signals in SKG mice are attenuated because of a point mutation in ZAP-70 (21), and differentiation of ␥/␦ T cells needs a strong signal via the TCR (48,49), there may be some defects in ␥/␦ T cell differentiation in SKG mice. This speculation was supported by data showing impaired development of specific subsets of ␥/␦ T cells in ZAP-70-knockout mice (50).…”
Section: Discussionmentioning
confidence: 99%
“…The thymus produces functional ab nTreg and gd T cells from common early precursors that follow distinct developmental pathways [7,26] but that end up sharing the unconventional property of being positively selected on high avidity signals [35][36][37][38], which presumably reflects their self-reactivity [21,39,40]. While the different homing properties of the two T-cell subsets may prevent their interaction in various tissues, gd cells may often come into contact with Treg in peripheral lymphoid organs, namely the spleen and lymph nodes (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%